Key Aspects Regarding the Recovery and Resilience Facility: Priorities, Risks and Perspectives - IULIA MONICA OEHLER-ŞINCAI (Global Economic Observer)
The main objective of this paper focuses on the analysis of the Recovery and Resilience Facility from the standpoint of general priorities and risks associated to less funds available for the Member States which are not able to accomplish some of their assumed milestones and targets. High shares of the total value of National Recovery and Resilience Plans are foreseen for the green and digital transitions. Health, education and social sectors, together with institutional development are also taken into account, however these are incomparably lower funded. In the literature are criticized, among others, the strings attached to the disbursements, neglect of social implications, uneven regional distribution, difficulty to implement judicial or pension reform. Changes of the initial plans have been possible, as several countries have already submitted substantially changed plans, in terms of amounts, and/or targets. The European Commission has endorsed them, based on justified "objective circumstances". In spite of all risks and weaknesses, the NRRPs prompt economic recovery and reforms in the EU Member States, in line with the EU’s goals and objectives.